Discovery of an amylose-free starch mutant in cassava (Manihot esculenta Crantz) - Ceballos, H.; Sánchez, T.; Morante, N; Fregene, Martin A.; Dufour, D.L.; Smith, A.M.; Denyer, K; Pérez Velásquez, Juan Carlos; Calle, F.; Mestres, C. (American Chemical Society, 2007)
One of the objectives of the cassava-breeding project at CIAT is the identification of clones with special root quality characteristics. A large number of self-pollinations have been made in search of useful recessive traits. During 2006 harvests an S1 plant produced roots that stained brownish-red when treated with an iodine solution, suggesting that it had lower-than-normal levels of amylose in its starch. Colorimetric and DSC measurements indicated low levels (3.4%) and an absence of amylose in the starch, respectively. SDS-PAGE demonstrated the absence of GBSS enzyme in the starch from these roots. Pasting behavior was analyzed with a rapid visco-analyzer and resulted in larger values for peak viscosity, gel breakdown, and setback in the mutant compared with normal cassava starch. Solubility was considerably reduced, while the swelling index and volume fraction of the dispersed phase were higher in the mutant. No change in starch granule size or shape was observed. This is the first report of a natural mutation in cassava that drastically reduces amylose content in root starch.